Copper and chromium binding by Pseudomonas aeruginosa strain PA01 for implications of heavy metal detoxification and soil remediation: A computational approach - Shanmuga Priya Ramasamy; Priya Sundararajan; Muthukrishnan Pallikondaperumal; Ponmurugan Karuppiah; Saminathan Kayarohanam; Natarajan Arumugam; Ling Shing Wong; Sinouvassane Djearamane (Journal of King Saud University: Science)
Heavy metal pollution poses significant environmental and health risks due to the toxic effects of metals like copper and chromium at elevated concentrations. Despite their essential roles in trace amounts, these metals can be highly toxic. Bacteria such as Pseudomonas aeruginosa are promising candidates for bioremediation due to their robustness and adaptability. The objective of this study was to analyze and identify potential copper and chromium binding genes involved in metal detoxification in Pseudomonas aeruginosa PA01. The heavy metal binding protein identified as ferredoxin using MALDI-TOF/PMF-MS analysis was further characterized. The structure of the ferredoxin protein was elucidated using the SWISS-MODEL tool. Metal-binding domains were validated through a pattern search against UniProtKB/Swiss-Prot and UniProtKB/TrEMBL databases using the ScanProsite tool. Comparative sequence alignments were conducted between the copper-binding NosD gene of P. aeruginosa, the ferredoxin gene of P. aeruginosa PA01, and the chromium-binding iron hydrogenase 1 gene of Clostridium chromiireducens. The SWISS-MODEL analysis revealed alpha helices and beta sheets with key metal-coordinating amino acids (cysteine, glutamic acid, aspartic acid, histidine, and methionine). The ScanProsite tool confirmed the presence of a 4Fe-4S ferredoxin-type iron-sulphur binding domain essential for coordinating chromium and copper ions. Sequence alignments showed a 64.29 % similarity between the NosD gene and ferredoxin gene, and a 67 % identity between the iron hydrogenase 1 gene and ferredoxin gene, with correlations in amino acid residues involved in metal binding. These findings suggest that the ferredoxin gene could effectively bind heavy metal ions, offering potential applications in bioremediation of metal-polluted soils using Pseudomonas species. This study contributes to sustainable agricultural productivity by facilitating the targeted remediation of heavy metal-contaminated soils through biological means.